Perancangan Aplikasi Pencatatan Dan Monitoring Performa Transaksi Penjualan Cabang Waralaba Teh Manis Solo Berbasis Website (Studi Kasus : Teh Manis Solo Siska) - Nugroho, Kevin Teguh; Malabay (Fakultas Teknik Universitas Persada Indonesia YAI, 2025)
Teh Manis Solo is a franchise engaged in the beverage sales sector. Siska Andriyani, as the franchisee, purchaseda partnership package and owns three branches in three different locations. The first branch is located at Jl. PuloHarapan Indah, West Jakarta. The second branch is located at Jl. M Toha, Tangerang City, and the third branchis located at Jl. Prabu Siliwangi, Tangerang City. In running her business, Teh Manis Solo Siska faces severalchallenges, such as recording transactions from the three branches still using a manual system, sales transactionsnot being recorded in detail since the records are based on how many thermos were sold today, and each branch'stransaction data must be monitored through direct inspections. Consequently, the owner finds it difficult tomonitor and know the types of beverages sold at each branch and control the business processes at each TehManis Solo Siska branch. To address these issues, a web-based application for Sales Transaction Recording andFranchise Branch Transaction Performance Monitoring of Teh Manis Solo is being developed. Theprogramming language used for designing and developing the application is PHP (Hypertext Preprocessor)using the CodeIgniter framework, and data processing is done using MySQL. The development method used isthe Waterfall model. The data collection process that will be implemented includes direct observation,interviews, and literature study. The hope is that this application will solve the problems faced by the businessowner in the process of recording sales transactions, expenditures, and monitoring as well as controlling businessprocesses at each branch.